Metal ions in biomedically relevant macromolecular structures - Majorek, Karolina A.; Gucwa, Michal; Murzyn, Krzysztof; Minor, Wladek (Frontiers in Chemistry, 2024)
Understanding the functions of metal ions in biological systems is crucial for many aspects of research, including deciphering their roles in diseases and potential therapeutic use. Structural information about the molecular or atomic details of these interactions, generated by methods like X-ray crystallography, cryo-electron microscopy, or nucleic magnetic resonance, frequently provides details that no other method can. As with any experimental method, they have inherent limitations that sometimes lead to an erroneous interpretation. This manuscript highlights different aspects of structural data available for metal-protein complexes. We examine the quality of modeling metal ion binding sites across different structure determination methods, where different kinds of errors stem from, and how they can impact correct interpretations and conclusions.Many metalloproteins contain metal ions as integral components, while others bind them transiently in cellular processes like transport and signaling. Ions of metals like magnesium, iron, zinc, and copper are crucial components of enzymes, stabilizing their structure and providing their biological function, and each of them also plays multiple other roles in the body (Jomova et al., 2022). Calcium (Ca 2+ ) is the most abundant metal in the human body, most often associated with skeletal health, but it is also involved in muscle function, nerve transmission, and enzyme activity. Magnesium (Mg 2+ ) is also a cofactor in more than 300 enzymatic reactions and a multitude of cellular processes (Jahnen-Dechent & Ketteler, 2012). Working in concert, calcium and magnesium are essential for proper muscle contraction and relaxation (Potter et al., 1981), optimal nerve transmission and neuromuscular coordination (Kirkland et al., 2018), bone mineralization, and maintenance of normal bone (Rondanelli et al., 2021). It has been shown that stress can increase magnesium loss, and in turn, magnesium deficiency can further enhance susceptibility to stress, resulting in a magnesium and stress vicious circle (Pickering et al., 2020). Magnesium is also of interest for the potential prevention and treatment of numerous neurological disorders (Kirkland